Preparation method and application of coal tar-based hard carbon material
Through high-temperature carbonization treatment of coal asphalt and tetrabromophenyl anhydride, hard carbon materials with a closed pore structure are prepared, which solves the problem of poor sodium storage performance of sodium ion battery negative electrode materials, and achieves high specific capacity and good cycle stability. Industrialized production.
Patent Information
- Application Number
- CN202311669982.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-07
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-12-07
AI Technical Summary
Existing sodium ion battery negative electrode materials perform poorly when storing sodium, mainly due to the large Na+ embedded resistance and instability of Na-C compounds, and the low yield of hard carbon materials with biomass as the precursor, resulting in a lower specific capacity of sodium storage. .
Coal asphalt is used to mix with halogen-containing acid anhydrides (such as tetrabromophenyl anhydride) in a certain proportion, and after high-temperature carbonization treatment under argon protection, coal asphalt-based hard carbon materials with a closed pore structure and low graphitization are prepared. Regulate its microcrystalline structure and surface properties to improve sodium storage performance.
It achieves a high first-time charging specific capacity of 330.33 mAh g-1 and good cycle stability and rate performance, reducing production costs and is suitable for industrial large-scale preparation.
Smart Images

Figure CN117550585B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of negative electrode materials for metal ion batteries, and in particular relates to a method for regulating the microcrystalline structure of a coal tar pitch-based hard carbon material and an application thereof in sodium ion batteries. Background Art
[0002] Lithium-ion batteries occupy a large share in the global energy market due to their high energy density and good cycle stability, and have promoted the upgrading of electronic products and the rapid development of the information society. In recent years, the ever-expanding scale of the global energy market has led to a shortage of lithium resources and rising prices. The dual constraints of price factors and resource factors have seriously affected the development of the future large-scale energy storage market. Sodium-ion batteries, which use abundant and cheap sodium resources as the main raw material and have a "rocking chair" mechanism similar to lithium-ion batteries, have broad application prospects. As a key component of sodium-ion batteries, the structure and performance of negative electrode materials will directly affect the performance indicators of sodium-ion batteries such as energy density. Graphite is a relatively mature commercial negative electrode material in lithium-ion batteries, but it performs poorly when storing sodium, mainly due to Na + It has a larger radius, has a greater resistance to embedding into the graphite layer, and the formation of Na-C compounds is extremely unstable in thermodynamics. Therefore, other negative electrode materials besides graphite must be developed to meet the requirements of sodium ion batteries. Hard carbon material is an amorphous carbon material with a theoretical capacity of 300.33 mAh g when storing sodium. -1 . However, the precursors for producing hard carbon are mostly biomass with low yield. Coal chemical by-products represented by asphalt are used as the main raw materials. By utilizing their high carbon content and condensation of polycyclic aromatic hydrocarbon molecules, carbon materials can be obtained with high yield. This is also an effective way to efficiently and effectively utilize my country's coal chemical resources. However, this type of polycyclic aromatic hydrocarbon is easily graphitized during heat treatment, and the prepared carbon material has a relatively ordered microcrystalline structure and a small interlayer spacing, resulting in a low sodium storage capacity. This is a bottleneck problem for asphalt-based carbon materials for the negative electrode of sodium-ion batteries. Summary of the invention
[0003] In order to overcome the deficiencies in the prior art, the present invention aims to provide a method for preparing a coal tar pitch-based hard carbon material with low cost, scalable preparation, low graphitization degree and rich closed-pore structure, and sodium ion battery application. In order to achieve the above invention purpose and solve the problems in the prior art, the technical solution of the present invention is implemented as follows: The present invention provides a method for preparing a coal tar pitch-based hard carbon material, comprising the following steps:
[0004] (1) Coal tar pitch and halogen-containing acid anhydride substances are uniformly mixed and ground in a mortar according to a certain ratio to obtain a powder sample A; the mass ratio of the coal tar pitch to the halogen-containing acid anhydride substances is 2:(1-5);
[0005] The halogen-containing anhydride substances are tetrabromophthalic anhydride, tetrafluorophthalic anhydride, tetrachlorophthalic anhydride and tetraiodophthalic anhydride.
[0006] (2) Powder sample A was placed in a corundum boat and placed in the center of a tube furnace. Argon was pre-flowed for 30 min to remove the air in the clean tube. Under the protection of argon atmosphere, the tube furnace was used for crosslinking and high-temperature carbonization. The temperature was raised from room temperature to 350-400 °C at a certain heating rate. The pre-crosslinking time was 0.5-2 h, and then carbonized at a certain temperature. The temperature was kept for 1-3 h to prepare a coal tar-based hard carbon material with rich closed pore structure and wide interlayer spacing.
[0007] As a preferred technical solution of the present invention, in the method for preparing the negative electrode hard carbon material of a sodium ion battery:
[0008] In step (1), the mass ratios of coal tar pitch:tetrabromophthalic anhydride are 2:1, 1:1, 1:1.5, 1:2, and 1:2.5 respectively.
[0009] The carbonization temperature in step (2) is 1100~1300°C.
[0010] The heating rates in step (2) are 2, 5, and 10 °C min -1 .
[0011] The present invention also provides a half-cell prepared by using the above-mentioned carbon material, which comprises the following steps:
[0012] Negative electrode preparation: 80 mg of negative electrode carbon material, 10 mg of conductive carbon black, and 10 mg of polyvinylidene fluoride (PVDF) were ground in a mortar for 15 min, 200 μL of N-methylpyrrolidone (NMP) was added, and the mixture was ground for another 6 min to obtain a uniform slurry. The slurry was evenly coated on the surface of copper foil with a scraper and dried in vacuum at 120 °C for 12 h to obtain a loading of 1-1.5 mg cm -2 The negative electrode.
[0013] Assembly: In a glove box filled with an inert Ar atmosphere, the positive electrode shell, positive electrode sheet (sodium sheet), glass fiber diaphragm, electrolyte, negative electrode sheet, gasket, shrapnel, and negative electrode shell were stacked in order and sealed with a sealing machine. The electrolyte used sodium trifluoromethanesulfonate (NaCF3SO3) as the solute and diethylene glycol dimethyl ether (Degdme) as the solvent, with a concentration of 1 mol L -1 The solution is used as the electrolyte to complete the battery assembly.
[0014] Test: The battery test system is a blue battery test system, and the test voltage window is 0.001~3 V.
[0015] The beneficial effects of the present invention are: using tetrabromophthalic anhydride as a cross-linking and pore-forming agent to introduce a closed pore structure into the carbon material, regulating the surface properties and microcrystalline structure of the asphalt-derived carbon, and improving the sodium storage performance of the carbon material. During the high-temperature carbonization process, tetrabromophthalic anhydride can absorb excess hydrogen on condensed aromatic hydrocarbon molecules. The oxygen-containing phthalic anhydride groups of tetrabromophthalic anhydride itself inhibit the condensation of condensed ring molecules, expand the interlayer spacing, and facilitate the insertion / extraction of sodium ions. Compared with other processes, this process has a short process flow, a simple synthesis method, greatly reduces production costs, and is conducive to industrialization.
[0016] Based on solid-phase heat treatment, anhydride substances rich in halogen atoms such as Br, F, Cl, and I are mixed evenly with coal tar pitch, and dehydrogenation and crosslinking driven by high-temperature thermal field are used to obtain hard carbon negative electrode materials. Thanks to the regulation of anhydride substances on the microcrystalline structure and pore structure of carbon materials, the hard carbon material has a high conductivity at 30 mA·g -1 The first charge capacity of the sodium storage device was 330.33 mAh g -1 The first coulombic efficiency was 77.29%, and it also had good cycle stability and rate performance. The preparation method of this hard carbon material is simple, low-cost, and easy to scale up. It is also helpful to study the regulation and evolution mechanism of the microstructure and pore structure of hard carbon materials, laying the foundation for the large-scale preparation of negative electrode materials for sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The hard carbon negative electrode material for sodium ion battery prepared in Example 1-5 has a high conductivity at 30 mA·g -1 The second cycle charge and discharge curve under current density shows the optimal mass ratio of asphalt to tetrabromophthalic anhydride. 2:1, 1:1, 1:1.5, 1:2, and 1:2.5 in the figure represent the mass ratios of asphalt to tetrabromophthalic anhydride.
[0018] Figure 2 The hard carbon negative electrode materials for sodium ion batteries prepared in Examples 3, 6-9 have a high performance at 30 mA·g -1 The second cycle charge and discharge curve under current density shows the optimal carbonization temperature.
[0019] Figure 3 The hard carbon negative electrode material for sodium ion battery prepared in Examples 3, 10-11 is 30 mA·g -1 The second cycle charge and discharge curve under current density shows the optimal heating rate.
[0020] Figure 4 This is a high-resolution transmission electron microscopy (HRTEM) image of the sodium ion battery hard carbon negative electrode material prepared in Example 3.
[0021] Figure 5The assembled half-cell of the sodium ion battery hard carbon negative electrode material prepared in Example 3 has a voltage of 0.1 mV s -1 CV curve diagram under scanning rate.
[0022] Figure 6 The assembled half-cell of the sodium ion battery hard carbon negative electrode material prepared in Example 3 is at 30 mA g -1 Cyclic performance test results under current density.
[0023] Figure 7 The assembled half-cell of the sodium ion battery hard carbon negative electrode material prepared in Comparative Example 1 was subjected to 30 mA g -1 The second cycle charge and discharge curve under current density.
[0024] Figure 8 The assembled half-cell of the sodium ion battery hard carbon negative electrode material prepared in Comparative Example 2 was 30 mA g -1 The second cycle charge and discharge curve under current density. Implementation
[0025] The present invention will be further described below in conjunction with the embodiments. Example 1
[0026] (1) Take 400 mg of asphalt and 200 mg of tetrabromophthalic anhydride, mix and grind them evenly in a mortar to obtain powder sample A;
[0027] (2) Place the powder sample A in a corundum boat and place it in the center of a tube furnace. Pre-flow argon for 30 min to remove the air in the clean tube. Under the protection of argon atmosphere, use a tube furnace for crosslinking and high-temperature carbonization, starting from room temperature at 5 °C min -1 The heating rate was raised to 400 °C, the pre-crosslinking time was 1 h, and then the temperature was raised to 1200 °C for carbonization, and the temperature was kept for 2 h to prepare the sodium ion battery hard carbon negative electrode material. The electrochemical performance of the sodium ion battery hard carbon negative electrode material prepared in Example 1 was 30 mA g -1 At a current density of 2.5 %, its first charge specific capacity can reach 210.24 mAh g -1 , the first Coulombic efficiency is 68.82%. Example 2
[0028] (1) Take 400 mg of asphalt and 400 mg of tetrabromophthalic anhydride, mix and grind them evenly in a mortar to obtain powder sample A;
[0029] (2) Place the powder sample A in a corundum boat and place it in the center of a tube furnace. Pre-flow argon for 30 min to remove the air in the clean tube. Under the protection of argon atmosphere, use a tube furnace for crosslinking and high-temperature carbonization, starting from room temperature at 5 °C min-1 The heating rate was raised to 400 °C, the pre-crosslinking time was 1 h, and then the temperature was raised to 1200 °C for carbonization, and the temperature was kept for 2 h to prepare the sodium ion battery hard carbon negative electrode material. The electrochemical performance of the sodium ion battery hard carbon negative electrode material prepared in Example 2 was 30 mA g -1 At a current density of 2.5 mAh g, its first charge capacity can reach 273.45 mAh g -1 , the first Coulombic efficiency is 67.55%. Example 3
[0030] (1) Take 400 mg of asphalt and 600 mg of tetrabromophthalic anhydride, mix and grind them evenly in a mortar to obtain powder sample A;
[0031] (2) Place the powder sample A in a corundum boat and place it in the center of a tube furnace. Pre-flow argon for 30 min to remove the air in the clean tube. Under the protection of argon atmosphere, use a tube furnace for crosslinking and high-temperature carbonization, starting from room temperature at 5 °C min -1 The heating rate was raised to 400 °C, the pre-crosslinking time was 1 h, and then the temperature was raised to 1200 °C for carbonization, and the temperature was kept for 2 h to prepare the sodium ion battery hard carbon negative electrode material. The electrochemical performance of the sodium ion battery hard carbon negative electrode material prepared in Example 3 was 30 mA g -1 At a current density of 1.3 mAh g, its first charge capacity can reach 330.3 mAh g -1 , the first Coulombic efficiency is 77.29%. Example 4
[0032] (1) Take 400 mg of asphalt and 800 mg of tetrabromophthalic anhydride, mix and grind them evenly in a mortar to obtain powder sample A;
[0033] (2) Place the powder sample A in a corundum boat and place it in the center of a tube furnace. Pre-flow argon for 30 min to remove the air in the clean tube. Under the protection of argon atmosphere, use a tube furnace for crosslinking and high-temperature carbonization, starting from room temperature at 5 °C min -1 The heating rate was raised to 400 °C, the pre-crosslinking time was 1 h, and then the temperature was raised to 1200 °C for carbonization, and the temperature was kept for 2 h to prepare the sodium ion battery hard carbon negative electrode material. The electrochemical performance of the sodium ion battery hard carbon negative electrode material prepared in Example 4 was 30 mA g -1 At a current density of 2.5 %, its first charge specific capacity can reach 288.07 mAh g -1 , the first Coulombic efficiency is 76.97%. Example 5
[0034] (1) Take 400 mg of asphalt and 1000 mg of tetrabromophthalic anhydride, mix and grind them evenly in a mortar to obtain powder sample A;
[0035] (2) Place the powder sample A in a corundum boat and place it in the center of a tube furnace. Pre-flow argon for 30 min to remove the air in the clean tube. Under the protection of argon atmosphere, use a tube furnace for crosslinking and high-temperature carbonization, starting from room temperature at 5 °C min -1 The heating rate was raised to 400 °C, the pre-crosslinking time was 1 h, and then the temperature was raised to 1200 °C for carbonization, and the temperature was kept for 2 h to prepare the sodium ion battery hard carbon negative electrode material. The electrochemical performance of the sodium ion battery hard carbon negative electrode material prepared in Example 5 was 30 mA g -1 At a current density of 2.5 mAh g, its first charge capacity can reach 277.57 mAh g -1 , the first Coulombic efficiency is 74.68%.
[0036] See also Figure 1 , which is the second cycle charge-discharge curve of the sodium ion hard carbon negative electrode material prepared in Examples 1-5. By comparing the electrochemical performance of the sodium ion battery hard carbon negative electrode materials prepared in Examples 1-5, the electrochemical performance of Example 3 is the highest, at 30 mA g -1 At a current density of 1.34 mAh g, its first charge capacity can reach 330.33 mAh g -1 , the first Coulombic efficiency is 77.29%. Example 6
[0037] On the basis of Example 3, keeping other conditions unchanged, the carbonization temperature in step (2) of Example 3 was changed to 1100°C to prepare a hard carbon negative electrode material for a sodium ion battery. The electrochemical performance of the hard carbon negative electrode material for a sodium ion battery prepared in Example 6 was -1 At a current density of 2.547 W, its first charge capacity can reach 252.97 mAh g -1 , the first Coulombic efficiency is 67.05%. Example 7
[0038] On the basis of Example 3, keeping other conditions unchanged, the carbonization temperature in step (2) of Example 3 was changed to 1150°C to prepare a hard carbon negative electrode material for a sodium ion battery. The electrochemical performance of the hard carbon negative electrode material for a sodium ion battery prepared in Example 7 was 30 mA g -1 At a current density of 2.5 %, its first charge capacity can reach 264.86 mAh g -1 , the first Coulombic efficiency is 67.58%. Example 8
[0039] On the basis of Example 3, keeping other conditions unchanged, the carbonization temperature in step (2) of Example 3 was changed to 1250°C to prepare a hard carbon negative electrode material for a sodium ion battery. The electrochemical performance of the hard carbon negative electrode material for a sodium ion battery prepared in Example 8 was 30 mA g -1 At a current density of 2.5 %, its first charge specific capacity can reach 296.98 mAh g -1 , the first Coulombic efficiency is 74.72%. Example 9
[0040] On the basis of Example 3, keeping other conditions unchanged, the carbonization temperature in step (2) of Example 3 was changed to 1300 °C to prepare a sodium ion battery hard carbon negative electrode material. The electrochemical performance of the sodium ion battery hard carbon negative electrode material prepared in Example 9 was 30 mA g -1 At a current density of 1.38 mAh g, its first charge capacity can reach 301.39 mAh g -1 , the first Coulombic efficiency is 74.18%.
[0041] See also Figure 2 , which is the second cycle charge-discharge curve of the sodium ion battery hard carbon negative electrode material prepared in Examples 3, 6-9. By comparing the sodium ion battery hard carbon negative electrode materials prepared in Examples 3, 6-9, it can be seen that the sodium ion battery hard carbon negative electrode material prepared under the conditions of Example 3 has the best electrochemical performance, at 30 mA g -1 At a current density of 1.34 mAh g, its first charge capacity can reach 330.33 mAh g -1 , the first Coulombic efficiency is 77.29%. Example 10
[0042] On the basis of Example 3, keeping other conditions unchanged, the heating rate in step (2) of Example 3 was changed to 2 °C min -1 , prepare the sodium ion battery hard carbon negative electrode material. The electrochemical performance of the sodium ion battery hard carbon negative electrode material prepared in Example 10 is 30 mA g -1 At a current density of 2.58 mAh g -1 , the first Coulombic efficiency is 60.43%. Embodiment 11
[0043] On the basis of Example 3, keeping other conditions unchanged, the heating rate in step (2) of Example 3 was changed to 10 °C min -1 , prepare the sodium ion battery hard carbon negative electrode material. The electrochemical performance of the sodium ion battery hard carbon negative electrode material prepared in Example 11 is 30 mA g -1At a current density of 2.5 %, its first charge capacity can reach 260.62 mAh g -1 , the first Coulombic efficiency is 73.18%.
[0044] See also Figure 3 , which is the second cycle charge-discharge curve of the sodium ion battery hard carbon negative electrode material prepared in Examples 3, 10, and 11. By comparing the sodium ion battery hard carbon negative electrode materials prepared in Examples 3, 10, and 11, it can be seen that the sodium ion battery hard carbon negative electrode material prepared under the conditions of Example 3 has the best electrochemical performance, at 30 mA g -1 At a current density of 1.34 mAh g, its first charge capacity can reach 330.33 mAh g -1 , the first Coulombic efficiency is 77.29%.
[0045] See also Figure 4 This figure is a HRTEM image of the sodium ion battery hard carbon negative electrode material prepared in Example 3. It can be seen from the figure that after high-temperature carbonization and tetrabromophthalic anhydride cross-linking, the sodium ion battery hard carbon negative electrode material presents a rich closed-pore structure and long-range graphite region.
[0046] See also Figure 5 This figure shows the half-cell assembled based on the hard carbon negative electrode material of the sodium ion battery in Example 3 at 0.1 mV s -1 CV curves at different scan rates. As shown in the figure, the redox peak near 0 V is very sharp, and the CV curves of the first five cycles are highly overlapped, indicating the reversible insertion / extraction behavior of sodium ions in the material.
[0047] See also Figure 6 This figure shows the half-cell assembled based on the hard carbon negative electrode material of the sodium ion battery in Example 3 at 30 mA g -1 Cyclic performance test results under current density. As shown in the figure, at 30 mA g -1 At a current density of 1.34 W, after 30 cycles, its charge capacity can still reach 300.9 mAh g -1 . Comparative Example 1
[0048] Based on Example 3, other conditions remain unchanged and tetrabromophthalic anhydride is replaced with phthalic anhydride. Figure 7 , which is the second cycle charge-discharge curve of the hard carbon negative electrode material for sodium ion battery prepared in Comparative Example 1. The electrochemical performance of the hard carbon negative electrode material for sodium ion battery prepared in Comparative Example 1 is shown at 30 mA g -1 At a current density of 1.34 W, its first charge capacity can reach 149.42 mAh g -1 , the first Coulombic efficiency is 67.90%. Comparative Example 2
[0049] Based on Example 3, other conditions were kept unchanged and tetrabromophthalic anhydride was not added. Figure 8 , which is the second cycle charge-discharge curve of the hard carbon negative electrode material for sodium ion battery prepared in Comparative Example 2. The electrochemical performance of the hard carbon negative electrode material for sodium ion battery prepared in Comparative Example 2 is shown at 30 mA g -1 At a current density of 1.54 mAh g, its first charge capacity can reach 156.53 mAh g -1 , the first Coulombic efficiency is 59.18%.
[0050] The battery performance test results show that the sodium ion battery hard carbon negative electrode material provided by the present invention has excellent electrochemical properties, among which tetrabromophthalic anhydride regulates the pore structure, microcrystalline structure and surface chemical properties of the carbon material. Because the presence of Br atoms will absorb the H atoms on the asphalt and release them to build a rich closed-pore structure in the carbon material. At the same time, the oxygen-containing phthalic anhydride group can not only inhibit graphitization, but also provide active oxygen groups to store sodium ions. Based on this feature, the sodium ion battery hard carbon negative electrode material has the advantages of high specific capacity, good cycle stability and good rate performance.
Claims
1. A method for preparing a coal tar-based hard carbon material, characterized in that: The steps include: (1) Coal tar pitch and tetrabromophthalic anhydride are uniformly mixed and ground in a mortar to obtain a powder sample A; the mass ratio of the coal tar pitch to the tetrabromophthalic anhydride is 2:(1-5); (2) placing the powder sample A in a corundum boat and placing it in a tubular furnace, pre-passing argon gas; under the protection of the argon atmosphere, heating to 350-400°C, pre-crosslinking for 0.5-2h, and then heating to 1100-1300°C for carbonization, holding the temperature for 1-3h, to obtain a coal tar-based hard carbon material; the heating rate in step (2) is 5 or 10°C min -1 .
2. The method for preparing a coal tar pitch-based hard carbon material according to claim 1, characterized in that: In step (1), the mass ratio of coal tar pitch to tetrabromophthalic anhydride is 2:1, 1:1, 1:1.5, 1:2 or 1:2.5 respectively.
3. The use of the coal tar pitch based hard carbon material prepared by the method according to claim 1 or 2, characterized in that: The coal tar pitch-based hard carbon material is applied in sodium ion batteries.
Citation Information
Patent Citations
High-rate hard carbon negative electrode material and preparation method and application thereof
CN115849332A
Negative electrode material and preparation method and application thereof
CN116960329A
Cited By
Hard carbon material, preparation method and application thereof, and sodium ion battery
CN121769080A